Preparation and partial ammonia demethylation of pectin from kamias (Averrhoa bilimbi Linn.) - Savella, Nadine Rosario B.; Acevedo, Teresita P. (1979.)
Low methoxyl pectin from kamias was evaluated in this study. Its production involved several steps namely extraction, precipitation, purification and the partial ammonia demethylation of the extracted pectin. The pectin was characterized in terms of its percent yield, percent methoxyl content, degree of esterification, and equivalent weight before and after demethylation. The pectin initially gave a yield of 7.43% which was reduced to 3.63%. A similar trend was also followed by the other parameters showing a decrease after demethylation. The amount of methyl groups decreased from 7.88% to 3.52%, the degree of esterification from 48.28% to 20.96%, and the equivalent weight from 440.68 g-eq to 218.50 g-eq. The setting due time of the jellies using commercial pectin and the low methoxyl pectin produced was compared. The lox methoxyl kamis gel set in 14.75 minutes as against 22 minutes of the standard jelly. This indicated that the former was a rapid set type while the latter was a slow set type.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Kamias; Pectin